2011
DOI: 10.1111/j.1469-0691.2010.03346.x
|View full text |Cite
|
Sign up to set email alerts
|

Sandfly fever virus activity in central/northern Anatolia, Turkey: first report of Toscana virus infections

Abstract: Sandfly fever viruses (SFVs) cause febrile diseases as well as aseptic meningitis/encephalitis and include serotypes sandfly fever Sicilian virus (SFSV), sandfly fever Naples virus (SFNV) and Toscana virus (TOSV). Infections are endemic in the Mediterranean basin and data on SFV activity in Turkey are limited. In this study, sera from 1533 blood donors from the Ankara, Konya, Eskisehir and Zonguldak provinces of Turkey were evaluated for SFV exposure by indirect immunofluorescence test (IIFT) and confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 25 publications
8
79
0
8
Order By: Relevance
“…Nevertheless, viral RNA detection has been established as a powerful tool and an effective alternative for identifying acute TOSV infections (Charel et al 2005). The impact of viral RNA detection in TOSV-associated central nervous system infections in the study region has also been documented recently, where TOSV IgM was identified via IIFT in only 4 (25%) of the 16 TOSV RNA positive sera (Ergü nay et al 2010). For TOSV IgG, the commercial assays evaluated in this study were observed to display slight to fair agreement with an average percentage of 57.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, viral RNA detection has been established as a powerful tool and an effective alternative for identifying acute TOSV infections (Charel et al 2005). The impact of viral RNA detection in TOSV-associated central nervous system infections in the study region has also been documented recently, where TOSV IgM was identified via IIFT in only 4 (25%) of the 16 TOSV RNA positive sera (Ergü nay et al 2010). For TOSV IgG, the commercial assays evaluated in this study were observed to display slight to fair agreement with an average percentage of 57.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples reactive for SFV IgG by a commercial IIFT (SFV IgG mosaic I; Euroimmun) performed during a serosurveillance study in Central Anatolia, Turkey, were employed in the study (Ergü nay et al 2010). The samples originated from healthy blood donors and were obtained after informed consent.…”
Section: Samples and Commercial Assaysmentioning
confidence: 99%
“…İç Anadolu ve Karadeniz bölgelerinde yapılan bir çalışmada; Ankara, Konya, Eskişehir ve Zonguldak bölgelerinde pozitifl ik oranları sırasıyla, %20.7, %65.9, %21.6 ve %29.6 olarak bildirilmiştir 10 . Virus serotipine göre dağılımlar incelendiğinde, en sık olarak %51.6 ile SFSV, ardından SFCV (%47.3), SFNV (%46.4) ve TOSV (%43.7) izlenmiştir.…”
Section: Aynı Yöntem (Iift) Ileunclassified
“…Interestingly, the evaluated sera were collected n 1955, indicating even an earlier activity of these viruses in the Mediterranean parts of Anatolia. 40 Seroprevalence rates of 0.84% for SFSV 42 This study demonstrated TOSV neutralizing antibodies in residents of all provinces investigated. In a following seroepidemiology study, VNT-confirmed TOSV seroreactivity of 5.2% was observed, verifying virus circulation in Central Anatolian provinces of Ankara and Eskişehir and further demonstrated TOSV circulation in residents from other provinces (Kırıkkale, Çorum and Kayseri) of this region.…”
Section: Seroepidemiology and Vector Surveillance In Anatoliamentioning
confidence: 95%
“…Partial sequence analyses performed in selected samples demonstrated the infecting isolate to be phylogenetically grouped with TOSV genotype A strains. 42 Subsequently, probable TOSV infections were identified in Izmir and Ankara provinces during the sandfly season in the following year, with similar clinical presentation and laboratory evaluation. 32 In a 43 year-old HIVinfected resident of Istanbul province, admitted to the hospital in Adana with high fever, headache, malaise, leucopenia, anemia and trombocytopenia, TOSV RNA was detected, suggesting virus circulating in Northwestern Anatolia.…”
mentioning
confidence: 99%